Determinants Of Earnings Management In Industrial Sector Companies Listed On The Indonesian Stock Exchange - Mohamad Zulman Hakim; Dhia Aufa Anshori; Wati Yaramah; Dewi Rachmania; Hesty Erviani Zulaecha; Ahmad Jayanih (International Journal of Economics, Business and Innovation Research, 2022)
This research was conducted with the aim of empirically proving the effects of Profitability, Leverage, and Firm Size on Earnings Management. The variables in this study are measured by Return on Asset, Debt to Asset Ratio, Natural Total Asset Logarithm, and Stubben's Conditional Revenue Model. The population in this study used the industrial sector listed on the Indonesia Stock Exchange for the period 2019 – 2021. The sampling technique used a purposive sampling method with several sample criteria, resulting in 15 companies being sampled in this study. The data analysis method in this study uses panel data regression analysis. The results of this study indicate that Profitability has a negative effect on Earnings Management. Leverage has no effect on Earnings Management and Firm Size has no effect on Earnings Management.